Pendidikan Karakter di Era Revolusi 4.0 pada Masa Pandemi (Current Research in Education: Conference Series Journal, 2022)
The problems surrounding morality have become common ideas, a morality crisis marked by an increase in crime, one of which is in the field of technology. So that this problem needs to be implemented character education in schools, the application of character education is not only to make students smart but also to make students behave well and not deviate. Character education is a process of coaching students so that behavior changes occur. During this pandemic, Character Education in schools is a challenge for teachers and parents, where at times like this Morality must be maintained in order to avoid unwanted things. Because technology is often used by students, technology has become an inseparable part of human life. Almost all aspects of supporting human life use technology, for example information technology, which can act as a learning medium and other support to obtain the necessary information and knowledge. Through this SWOT analysis technique with qualitative methods can produce weaknesses and threats to become a strength and opportunity for character education in the revolutionary era 4.0. The conclusion is that the SWOT analysis can produce a revision of character education that is relevant for changes in the future of the nation's children for the better.